Whooo knew? : the truth about owls - Whipple, Annette (Whipple, Annette. Truth about --, 2020)
How do owls see in the dark? Can owls spin their heads all the way around? Why do owls puke? These and other questions are answered along with some extra information provided by the owls themselves!